Efeito da temperatura dos géis clareadores em suas propriedades físico-químicas, no substrato e na eficiência estética - Terada, Tatiane Ayumi Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Os géis clareadores, à base de peróxido de hidrogênio ou de carbamida, são sensíveis à luz, ao calor e à umidade. O armazenamento inadequado acelera sua degradação, diminuindo a liberação de oxigênio ativo, agente fundamental para o clareamento dental. Este estudo teve como objetivo avaliar o impacto de diferentes temperaturas (5°C, 25°C e 40°C) sobre a ação dos géis clareadores, considerando alteração cromática, difusão trans-amelodentinária, rugosidade, microdureza, viscosidade e liberação de espécies reativas de oxigênio (EROs). Foram utilizados 60 incisivos bovinos (n=15), de animais abatidos com idade entre 24 e 36 meses. Na fase 1, discos de esmalte/dentina de incisivos bovinos (n=15; 5,7 mm de diâmetro e 3,5 mm de espessura) foram divididos em quatro grupos: controle, gel a 5°C, 25°C e 40°C. As análises foram feitas em cinco momentos: Baseline, após a 1ª, 2ª e 3ª sessões, e após 14 dias. A alteração cromática foi avaliada com espectrofotômetro UV-Vis, e a difusão trans- amelodentinária por método enzimático durante a primeira sessão. Na fase 2, novos espécimes não pigmentados, preparados conforme a fase 1, foram avaliados quanto à rugosidade e microdureza antes e após as três sessões. Na fase 3, foram realizadas análises físico-químicas dos géis. A viscosidade foi determinada com viscosímetro Brookfield DV2T, e a liberação de EROs, pela sonda carboxy-H2DCFDA, com leituras de fluorescência (excitação: 492 nm; emissão: 527 nm). A análise estatística foi realizada no software SigmaPlot 12.0, com nível de significância de 5%. Após a análise dos resultados, o gel clareador a 40°C apresentou a maior eficácia estética, porém com os maiores danos ao substrato dentário e às propriedades físico-químicas. Em contrapartida, o gel a 5°C causou menos danos, mas com menor desempenho clareador. Já o gel a 25°C mostrou-se como a melhor opção, promovendo clareamento satisfatório e alterações estruturais intermediárias. Assim, conclui- se que a temperatura a 25°C representa um equilíbrio entre eficácia estética e preservação do substrato.

Bleaching gels, composed mainly of hydrogen peroxide or carbamide peroxide, are chemically sensitive to factors such as light, heat and humidity. Improper storage can accelerate the degradation of these compounds, reducing the capacity to release active oxygen, the essential agent for the dental bleaching process. Thus, this study aims to evaluate the impact of different temperatures (5°C, 25°C and 40°C) on the action of bleaching gels, considering chromatic alteration, trans-enamel-dentin diffusion, roughness, microhardness, viscosity and release of ROS. Sixty bovine incisors (n=15) from animals slaughtered between 24 and 36 months of age were used. In phase 1, samples of bovine incisors (n=15) on enamel/dentin discs (5.7 mm in diameter and 3.5 mm in thickness) were divided into four experimental groups: control, gel at 5°C, 25°C and 40°C. Each group was evaluated at five moments: Baseline, after the 1st, 2nd and 3rd sessions and after 14 days. The color change was measured with a UV-Vis spectrophotometer 48 hours after each session and 14 days after the end. The trans- amelodentinal diffusion was measured by an enzymatic method during the first session. In phase 2, new, non-pigmented specimens were prepared according to phase 1 and divided into the same experimental groups. These specimens were evaluated for roughness and microhardness before and after the three bleaching sessions. In phase 3, focused on the physicochemical evaluations of the bleaching gel, the viscosity was measured with a Brookfield DV2T viscometer. The formation of reactive species was measured by the carboxy-H2DCFDA probe, with fluorescence readings at 492 nm excitation and 527 nm emission. Statistical analysis was performed using SigmaPlot 12.0 software, adopting a significance level of 5%. After analyzing the results, the whitening gel at a hot temperature (40°C) led both in aesthetic efficacy and in substrate changes and physical-chemical properties. The whitening gel at a cold temperature (5°C) resulted in less damage, but its aesthetic efficacy presented lower results. Therefore, the whitening gel at room temperature (25°C) showed satisfactory color change and whitening index and, at the same time, intermediate structural damage, being therefore the best option among the groups studied. Therefore, the different temperatures of whitening gels influence the following aspects: aesthetic efficacy, substrate changes and physical-chemical properties of the tooth structure.
Effect of temperature of whitening gels on their physicochemical properties, substrate and aesthetic efficacy
Keywords: Dentes Clareamento; Peróxido de hidrogênio; Temperatura; Hydrogen peroxide